A tactile feedback insertion strategy for peg-in-hole tasks - Gibbons, O; Albini, A; Maiolino, P (IEEE, 2023)
The Peg-In-Hole (PiH) task performed under un-certain conditions still represents a challenge for autonomous robots. When the peg is not rigidly connected to the robot end-effector, the external forces generated by peg-environment interactions can change the in-hand pose of the peg. This aspect must be taken into account when performing the insertion. This paper deals with this problem and proposes an insertion strategy driven by tactile feedback. In particular, we consider holding the peg using a parallel gripper equipped with tactile sensors, whose measurements are processed to capture in-hand rotations of the peg pose. This information is fed back to the robot controller and used to compensate for changes in the peg orientation and end-point position occurring during the task execution. The approach is validated on a real robot using a two-finger gripper equipped with two capacitive-based tactile sensor arrays hosting 20 tactile elements each. We show that the proposed method achieves an insertion success rate of 38/40 with a 0.1 mm clearance between the peg and hole.